Challenges in early childhood care and education in impoverished rural communities in KwaZulu-Natal Province, South Africa - Ashnie Mahadew (Interdisciplinary Journal of Rural and Community Studies)
Thirty years after the abolishment of apartheid in South Africa, socio-economic inequalities persist, resulting in a life of adversity for most young children living in poverty. This is despite the government’s vision for 2030, which recognises the potential of early childhood care and education (ECCE) to alleviate poverty and inequality. Society's most vulnerable members need access to quality ECCE programmes to realise this vision. One of the main aspects of quality in ECCE is a professional workforce, a play-based curriculum, a safe environment, and parent and community partnerships. This article reports on a case study that aims to explore the experiences of ECCE personnel in impoverished and marginalised rural communities in KwaZulu-Natal Province. Data were generated from photographs, written narratives, and semi-structured interviews based on their experiences in rural ECCE centres. Despite recognising ECCE as a critical foundation for the optimal development of children, the findings reveal that numerous challenges plague the centres in these areas. The findings highlight poor infrastructure, nutrition, and service delivery, as well as the intricate interplay between ecological systems and Maslow’s hierarchy of needs in shaping the quality of ECCE for young children. To achieve the goals of the National Development Plan, the study recommends that the government prioritise investment in ECCE programmes and support and collaborate with non-governmental organisations, especially in marginalised areas of KwaZulu-Natal.